Advances in Endoscopy in Inflammatory Bowel Disease (Springer Japan, 2018)
Advances in Endoscopy in Inflammatory Bowel Disease summarizes the recent progress made in endoscopy, an essential tool for the diagnosis and management of IBD. It goes on to provide an introduction of state-of-the-art endoscopic techniques, as well as an atlas of high-quality endoscopic images of IBD and related diseases. Among others, endoscopy is one of the clinical fields in which Asian countries are leading the way in the management of gastrointestinal disorders. As the number of patients with IBD is dramatically increasing in Asia, quality of patient care has been significantly improved. With diagnosis of intestinal Behcet, simple ulcers, and intestinal tuberculosis, which are unique to the Asian countries, this book offers the ideal standard textbook for IBD endoscopy in all Asian counties, while the superior quality of images also makes it a valuable resource for practitioners around the globe. This book will significantly help all physicians, endoscopists and researchers working on GI endoscopy, especially those focusing on IBD, to improve their knowledge of IBD endoscopy.